Migratory preferences of humpback whales between feeding and breeding grounds in the eastern South Pacific. Issue 4 (9th June 2017) - Acevedo, Jorge; Aguayo‐Lobo, Anelio; Allen, Judith; Botero‐Acosta, Natalia; Capella, Juan; Castro, Cristina; Rosa, Luciano Dalla; Denkinger, Judith; Félix, Fernando; Flórez‐González, Lilian; Garita, Frank; Guzmán, Héctor M.; et al.
Abstract: Latitudinal preferences within the breeding range have been suggested for Breeding Stock G humpback whales that summer in different feeding areas of the eastern South Pacific. To address this hypothesis, humpback whales photo‐identified from the Antarctic Peninsula and the Fueguian Archipelago (southern Chile) were compared with whales photo‐identified from lower latitudes extending from northern Peru to Costa Rica. This comparison was performed over a time span that includes 18 austral seasons. A total of 238 whales identified from the Antarctic Peninsula and 25 whales from the Fueguian Archipelago were among those photo‐identified at the breeding grounds. Our findings showed that humpback whales from each feeding area were resighted unevenly across the breeding grounds, which suggests a degree of spatial structuring in the migratory pathway. Humpback whales that feed at the Antarctic Peninsula were more likely to migrate to the southern breeding range between northern Peru and Colombia, whereas whales that feed at the Fueguian Archipelago were more likely to be found in the northern range of the breeding ground off Panama. Further photo‐identification efforts and genetic sampling from poorly sampled or unsampled areas are recommended to confirm these reported connectivity patterns.